2021
DOI: 10.3233/jad-210025
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Psychological Burden Among Family Caregivers of People Living with Alzheimer’s Disease Using the Zarit Burden Interview

Abstract: Background: In China, family caregivers play a major role in caring for people living with Alzheimer’s disease (PLWAD), but little is known about the burden this creates. Objective: This study aimed to investigate the burden among family caregivers of PLWAD and the factors influenced it. Methods: Family caregivers of PLWAD were recruited from a hospital in China from January 2018 to July 2018. All data were collected online using the Chinese version of the Zarit Burden Interview (ZBI), and the participants’ so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Of the 23 studies, 8 ( 14 , 21 – 27 ) (34.8%) were in English and 15 ( 15 – 17 , 28 – 39 ) (65.2%) were in Chinese. In addition, 14 studies ( 14 – 16 , 21 , 23 , 27 – 29 , 32 , 34 – 39 ) (60.9%) employed Caregiver Burden Inventory (CBI), 7 ( 17 , 22 , 24 26 , 31 , 33 ) (30.4%) employed Zarit Burden Interview (ZBI), 1 ( 30 ) (4.3%) employed Family Burden Scale (FBS), and 1 ( 15 ) (4.3%) employed Perceived Stress Scale (PSS). This review included 4,076 participants, and the sample sizes ranged from 94 to 335.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 23 studies, 8 ( 14 , 21 – 27 ) (34.8%) were in English and 15 ( 15 – 17 , 28 – 39 ) (65.2%) were in Chinese. In addition, 14 studies ( 14 – 16 , 21 , 23 , 27 – 29 , 32 , 34 – 39 ) (60.9%) employed Caregiver Burden Inventory (CBI), 7 ( 17 , 22 , 24 26 , 31 , 33 ) (30.4%) employed Zarit Burden Interview (ZBI), 1 ( 30 ) (4.3%) employed Family Burden Scale (FBS), and 1 ( 15 ) (4.3%) employed Perceived Stress Scale (PSS). This review included 4,076 participants, and the sample sizes ranged from 94 to 335.…”
Section: Resultsmentioning
confidence: 99%
“…Studies ( 15 , 30 , 33 , 37 ) have indicated that 70.3–100% of family caregivers bear the burden of care. In addition, primary family caregivers in 14 studies ( 14 , 16 , 22 , 23 , 26 , 28 – 30 , 32 – 37 ) (60.9%) were offspring or other relatives and in six studies ( 15 , 24 , 25 , 27 , 31 , 38 ) (26.1%) were spouses, but three studies ( 17 , 21 , 39 ) (13%) were failed to mention the proportion of caregivers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer's disease (AD)-associated dementia accounts for 60–80% of dementia cases, and is a significant health concern in the elderly (Alzheimer's, 2018 ). Cognitive impairments are the main clinical manifestations of AD, and affect patients and caregivers, and increase societal burden (Yin et al, 2021 ). Drugs such as donepezil, rivastigmine, and galantamine commonly used for treatment if AD do not impact long-term prognosis (Liao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This test has 22 items on a five-point Likert type scale from 0 to 4, with higher scores indicating a higher burden. The scale measures the psychological burden and stress experienced by caregivers caring for people with dementia 15 . Depressive symptomatology CES-D (Center for Epidemiologic Studies Depression Scale) 16 .…”
Section: Methodsmentioning
confidence: 99%